Treatment outcome of tubercular lymphadenopathy cases treated under dots: a five year follow up study - Takhar, Rajendra P.; Kothari, Prateek; Luhadiya, Shanti K.; Gupta, Narendra K. (International Journal of Research in Medical Sciences, 2017)
Background: Treatment of tubercular lymphadenopathy consists of at least 6 months of therapy with antitubercular drugs as DOTS in India. Some studies recommend that extension of therapy for some time may lead to lesser recurrence and relapse. This study was planned to assess the outcome of DOTS therapy in lymph node tuberculosis (TB) cases treated under RNTCP and to find out the prevalence of relapse in these patients in southern Rajasthan. Methods: This was a retrospective analysis of 275 cases of lymph node tuberculosis treated with DOTS under RNTCP. An immediate outcome of these cases was recorded and further traceable 81 patients were interviewed for long term outcome. Results: In our study population, treatment completion rate was 93.09%, defaulter rate was 4% and death reported in 3.7% (3/81) cases. We observed relapse rate of 9.1% after treatment completion. A total of 7.04% patients received extended treatment and none of them had relapsed during our follow up. Conclusions: Our study confirms that the efficacy of DOTS treatment is quite good in cases of tubercular lymphadenopathy but still requires review of programmatic strategy. An extension of antitubercular therapy is recommended because patients treated with DOTS had a little higher relapse rate in comparison to whom the treatment extended who had no recurrence and relapse.